Systematic Literature Review: Kemampuan Pemecahan Masalah Matematis Peserta Didik dalam Pembelajaran Matematika - Meilani, Ajeng; Meiliasari (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
The ability to solve mathematical problems is essential for students to develop into quality individuals. This study aims to describe the definition, indicators, and ways to improve problem-solving skills in students. Systematic Literature Review (SLR) is the method applied in this article. There are 20 articles that have been reviewed, but only 12 articles in the last 5 years that match the criteria for study materials on students' skills in solving mathematical problems. The results of this article explain that 1) mathematical problem-solving ability is an ability that relies on students' intellectual abilities to be able to solve non-routine problems related to mathematics logically, carefully, critically, and in accordance with the stages that are in accordance with its rules; 2) indicators referred to in problem-solving ability come from Polya, Lynch and Wolcott, and John Dewey; and 3) how to strengthen problem-solving skills in mathematics by using appropriate learning models in this case are problem-based learning, creative-based learning, realistic mathematics education. In the continuation of the research, it is hoped that more theories can be found other than those referred to in this article from other researchers in the context of problem solving.